Using Motion Tracking to Analyze Forceps Paths During Simulated Forceps-Assisted Vaginal Deliveries. Issue 6 (December 2021) - Bramblet, Rachel; Altman, Alan; Holbert, Michael
Abstract : Objective: The purpose of this study was to evaluate the ability of motion tracking to discern variation in forceps paths during standardized simulated forceps-assisted vaginal deliveries among experienced and inexperienced obstetric providers. Methods: This is a pilot study involving 24 obstetrics and gynecology residents and 6 faculty at a single institution. Each participant was filmed performing standardized simulated forceps-assisted vaginal deliveries on a high-fidelity model. Motion tracking software (Kinovea, Medoc, France) was used to track the path of the forceps shank. Data were analyzed for total path length, total x-plane displacement, total y-plane displacement, and final forceps angle. One-way analysis of variance was used to evaluate for statistically significant differences between groups based on education year, with Turkey HSD post hoc test to identify interactions. Results: Statistically significant differences were noted between groups in the total path length ( F = 7.57, P < 0.001) and total y-plane displacement ( F = 5.79, P < 0.001). On pairwise comparison, significant differences were noted between faculty and postgraduate year 1 as well as faculty and postgraduate year 2 for total y-plane displacement and total path length. Significant differences were not observed between groups for total x-plane displacement ( F = 0.89, P = 0.475) and final forceps angle ( F = 2.45, P = 0.052). Conclusions: Motion tracking of standardized simulated forceps-assisted vaginal deliveries identifies statistically significant differences between experienced and inexperienced obstetric providers. Our findings suggest that motion tracking can be used to design an educational intervention to improve forceps technique among obstetrics and gynecology residents.